Customized Incubation Services and Growth of Tenants: The Mediating Effect of Behavior Orientation of Social Networking Services - Zhang, Li; Zhou, Yongtao (Frontiers in Psychology, 2021)
It focuses on customized services, behavior orientation of social networking services, and tenants’ growth. Firstly, it employs situational theory and contingency theory to analysis why customized services lead to behavior of social networking services; secondly, it explores why behavior of social networking services facilitate tenants’ growth based on co-production theory and social network theory; next, it conduct a research on the direct relationship between customized services and tenants’ growth anchoring on the theory of co-production, customer satisfaction and dynamic environment. Then it develops the theoretical model of mediating effect and conducts empirical test by means of structural equation model. Customized services facilitate tenants’ growth directly. While referring to the relationship among customized services, behavior of social networking services, and tenants’ growth, it could be drawn the conclusion that customized services facilitate tenants’ growth via behavior of social networking services, at the same time customized services had no direct impact on tenants’ growth. So the behavior of social networking services fully mediate the relationship between customized services and tenants’ growth. Accordingly, we should promote incubation services to be deeply embedded in social networking services, and incubator management should improve the capability to deal with big data embedded in social networking services. In additional, entrepreneurial ecosystems should be also embedded in social networks intensively.